Regiospecific Normal Diels–Alder Reaction of trans-1,2-Biscoumarinylethenes - Sanap, Kailas K.; Samant, Shriniwas D. (Synlett, 2012)
The reaction of different 7,8-substituted coumarin 4-acetic acids with 7-diethylaminocoumarin-3-carbaldehyde in the presence of piperidine in methanol gives 1,2-biscoumarinylethenes. These compounds undergo regiospecific Diels–Alder reactions at their electron-rich diene components C3–C4–C10–C9, with electron-deficient dienophiles. The feasibility of normal electron-demand Diels–Alder reactions could be explained on the basis of the HOMO–LUMO gap. All the compounds are new and are intensely colored.
Keywords: coumarins; cycloaddition reaction; Diels–Alder reaction; 3,4-annulated coumarin; regiospecific reaction